Legal Strategy for Intellectual Property Protection in the Era of Open-source and Creative Commons in Indonesia - Andrew Shandy Utama; Ade Pratiwi Susanty (Eastasouth Institute, 2023)
This study navigates Indonesia's shifting IP protection landscape by examining the advantages and challenges of coexisting traditional IP regimes with open-source projects and Creative Commons license. In this age of collaborative innovation, the article focuses on legal strategies for adjusting to the dynamic interplay between proprietary and open models. This study employs a mixed-methods approach, combining legal analysis, case studies, interviews, and surveys, to explore the impact of open-source dynamics, provide flexible legal solutions, and highlight the benefits and drawbacks of existing intellectual property laws. The study's findings contribute to the ongoing discussion about establishing a harmonious atmosphere that fosters innovation while upholding the rights of those who create. The creative community, lawmakers, and companies can all benefit from the recommendations.